2019
DOI: 10.1002/hbm.24802
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal fusion of structural and functional brain imaging in depression using linked independent component analysis

Abstract: Previous structural and functional neuroimaging studies have implicated distributed brain regions and networks in depression. However, there are no robust imaging biomarkers that are specific to depression, which may be due to clinical heterogeneity and neurobiological complexity. A dimensional approach and fusion of imaging modalities may yield a more coherent view of the neuronal correlates of depression. We used linked independent component analysis to fuse cortical macrostructure (thickness, area, gray mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 89 publications
0
30
1
Order By: Relevance
“…However, even with this potential drawback, they have shown promise in analyzing genomic datasets ( Arloth et al, 2020 ; Chen et al, 2019 ; Min et al, 2017 ; Tranchevent et al, 2019 ). Deep learning has enabled efficient multimodal neuroimaging fusion, capitalizing on the strength of each modality ( Maglanoc et al, 2020 ; Plis et al, 2014 ; Sui et al, 2012 ; Zhang et al, 2020 ). A convolutional neural network for co-expression was able to predict transcription factor targets, identify disease-related genes and perform causality inference in one framework ( Yuan and Bar-Joseph, 2019 ).…”
Section: Systems Biology Approachesmentioning
confidence: 99%
“…However, even with this potential drawback, they have shown promise in analyzing genomic datasets ( Arloth et al, 2020 ; Chen et al, 2019 ; Min et al, 2017 ; Tranchevent et al, 2019 ). Deep learning has enabled efficient multimodal neuroimaging fusion, capitalizing on the strength of each modality ( Maglanoc et al, 2020 ; Plis et al, 2014 ; Sui et al, 2012 ; Zhang et al, 2020 ). A convolutional neural network for co-expression was able to predict transcription factor targets, identify disease-related genes and perform causality inference in one framework ( Yuan and Bar-Joseph, 2019 ).…”
Section: Systems Biology Approachesmentioning
confidence: 99%
“…The MRI literatures on suicide attempt in MDD suggested alterations of both structure and function in the amygdala-PFC neural circuitry. Compared with single neuroimaging analysis, the multiple neuroimaging analyses such as combining functional connectivity, regional gray matter volume, as well as combining amplitude of low-frequency fluctuations and white matter connectivity, could be used not only to explore the local functional and structural abnormalities, but also to identify more precisely the key neural circuitry in the mental disorders, providing the evidence to better understand the the mechanism of mental disorders in-depth (29,(31)(32)(33). Additionally, the latest studies suggested that data from multimodal fusion of structural and functional brain imaging analyses may be helpful to specifically predict symptoms and treatment effects in mental diseases (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…Although the rates and trajectories vary substantially between individuals and cognitive domains (Ardila, 2007), normal aging is primarily associated with a decline in most cognitive functions, including executive functions, attention, memory and perception (Riddle, 2007). Numerous studies have established pronounced age-related differences in brain network connections (Betzel et al, 2014; Cassady et al, 2019; Dørum et al, 2017; Geerligs, Renken, Saliasi, Maurits, & Lorist, 2015; Grady, Springer, Hongwanishkul, McIntosh, & Winocur, 2006; Maglanoc, Kaufmann, van der Meer, et al, 2019; Meunier, Achard, Morcom, & Bullmore, 2009; Wang, Su, Shen, & Hu, 2012). However, so far mostly age-related network changes have been studied using static functional connectivity, where connectivity strengths are estimated from stationary coefficients and assumed not to change short-term during the period of scan.…”
Section: Introductionmentioning
confidence: 99%